2021
DOI: 10.1007/s10072-020-04954-w
|View full text |Cite
|
Sign up to set email alerts
|

Energy cost and psychological impact of robotic-assisted gait training in people with spinal cord injury: effect of two different types of devices

Abstract: Background: In the last years there has been an intense technological development of robotic devices for gait rehabilitation in spinal cord injury (SCI) patients. The aim of the present study was to evaluate energy cost and psychological impact during a rehabilitation programme with two different types of robotic rehabilitation systems (stationary system on treadmill, Lokomat and overground walking system, Ekso GT). Methods: Fifteen SCI patients with different injury levels underwent robot-assisted gait traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…However, this may be attributed to the 1.68 km•h −1 difference in walking speed or differences in the exoskeleton devices. Previous research also demonstrated increased HR data during powered exoskeleton assisted walking, and produced similar results (100 ± 13, 88-134, 72-132, and 115 bpm within a single participant) when compared to the current findings [11,14,15,47,48]. Evans et al [16] recorded HR over two exoskeleton walking bouts within a SCI population.…”
Section: Discussionsupporting
confidence: 85%
“…However, this may be attributed to the 1.68 km•h −1 difference in walking speed or differences in the exoskeleton devices. Previous research also demonstrated increased HR data during powered exoskeleton assisted walking, and produced similar results (100 ± 13, 88-134, 72-132, and 115 bpm within a single participant) when compared to the current findings [11,14,15,47,48]. Evans et al [16] recorded HR over two exoskeleton walking bouts within a SCI population.…”
Section: Discussionsupporting
confidence: 85%
“…Question 5 showed the highest score of the questionnaire with 4.86 ± 0.35 out of 5 points, which means that physiotherapists found that the EKSO GT ® had a positive impact in the patients’ gait, in accordance with other studies that showed improvements in gait, balance or better activity of the trunk muscles with EKSO GT ® [ 8 , 43 , 44 ]. In agreement with much of the literature on robotic exoskeletons, the type of the device used could influence walking capacity [ 45 ], since it has been observed that EKSO GT ® allows more work during session than grounded exoskeletons such as Lokomat [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we investigated the potential correlations between satisfaction and clinical data. While we are aware that some studies have evaluated satisfaction with EKSO GT ® in patients with spinal cord injury [ 35 ], to our best knowledge, this is the first study providing an evaluation of the satisfaction of training with EKSO GT ® in people with MS and the clinical staff involved.…”
Section: Discussionmentioning
confidence: 99%
“…This is a phenomenon that has been captured in the Lemaire et al (2017) research wherein patients with spinal cord injuries used lower extremity-powered exoskeletons. Other studies have found that patients expressed fatigue after rehabilitation that incorporated a treadmill component (Corbianco et al, 2021;Törnbom & Danielsson, 2018).…”
Section: Discussionmentioning
confidence: 99%